Uji Viabilitas, Vigor, dan Pendugaan Aksi Gen Varietas Tebu (Saccharum Officinarum L.) Berdasarkan Karakter Agronomi - Mayasari Yamin; Sri Nur Qadri; Taufiq Hidayat RS (Journal Galung Tropika, 2024)
Sugarcane seeding is a conventional initial seed stage that begins based on the juvenile phase for the formation of the three main components of the plant, namely roots, stems, and leaves. Conventional sugar cane nurseries use explants from either bud chips or mules to grow buds. Initial testing is based on viability characteristics, and seed vigor index. In addition, explant growth is influenced by the genetic aspects of each material used. This research aims to (1) determine the viability, and index of sugarcane seeds, and (2) estimate the action of genes that influence each observed character. This research was carried out in June – July 2023. The research used a complete randomized block design with the treatment of sugar cane varieties, namely AMS Agribun (V1), AAS Agribun (V2), and Kidang Kencana (V3). The results showed that the agronomic characters for the number of leaves, and leaf length were significantly different from ? 5%, with standard deviation, and coefficient of variation values, respectively, reaching 0.0697, and 21.144 for the number of leaves, and 4.743, and 29.776 for leaf length characters. The characters for the number, and length of leaves have skewness, and kurtosis values of 0.816, and (-0.3079), and 0.416, and (-0.811), respectively. The AMS Agribun variety showed the best performance for plant height, leaf length, leaf greenness, and number of roots. The AAS Agribun variety showed the best performance for the character’s number of leaves, leaf width, and leaf area. Meanwhile, the Kidang Kencana variety showed the best performance regarding vigor index, growth speed, germination capacity, and root length.